2001
DOI: 10.1002/1096-8628(20010801)102:2<161::aid-ajmg1453>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

GPC3 mutation analysis in a spectrum of patients with overgrowth expands the phenotype of Simpson-Golabi-Behmel syndrome

Abstract: Simpson-Golabi-Behmel syndrome (SGBS) is an X-linked overgrowth syndrome caused by deletions in glypican 3 (GPC3). SGBS is characterized by pre- and postnatal overgrowth, a characteristic facial appearance, and a spectrum of congenital malformations which overlaps that of other overgrowth syndromes. We performed GPC3 deletion screening on 80 male patients with somatic overgrowth in the following categories: SGBS (n = 19), possible SGBS (n = 26), including families in which individuals had previously been diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 42 publications
5
60
0
Order By: Relevance
“…9 In addition to visceral and skeletal abnormalities, SimpsonGolabi-Behmel patients have increased incidence of embryonal tumors (Wilms' tumor, neuroblastoma and hepatoblastoma). 8,10 This combination of findings suggested that glypican-3 has an inhibitory effect on cell proliferation and could function as a tumor-suppressor gene. 11 Indeed, few tumors, including ovarian carcinoma, 12 mesothelioma 13 and breast carcinoma, 2,14 show lower glypican-3 expression relative to normal tissue.…”
supporting
confidence: 76%
“…9 In addition to visceral and skeletal abnormalities, SimpsonGolabi-Behmel patients have increased incidence of embryonal tumors (Wilms' tumor, neuroblastoma and hepatoblastoma). 8,10 This combination of findings suggested that glypican-3 has an inhibitory effect on cell proliferation and could function as a tumor-suppressor gene. 11 Indeed, few tumors, including ovarian carcinoma, 12 mesothelioma 13 and breast carcinoma, 2,14 show lower glypican-3 expression relative to normal tissue.…”
supporting
confidence: 76%
“…For example, we found genes/gene families involved in UB branching and growth, such as BMP7 [19,20]; UB elongation and epithelial maturation, such as Pod1, HSPG, and MDK; and renin and extracellular matrix/matrix protease genes that participate in epithelial formation and vascular patterning [21,22] were decreased in RD. Expression of a number of genes implicated in human syndromes with abnormal renal phenotype (SALL1, GPC3, AGTR2, WNT5A, and renin) was also decreased in RD kidney samples [23][24][25][26][27]. Decreased expression of these genes in the kidneys in RD in our study reiterates their importance in normal kidney development and suggests their loss may contribute to pathogenesis of RD, not only in heritable human disorders but also in patients with sporadic congenital RD.…”
Section: Discussionmentioning
confidence: 53%
“…Currently, data suggest that GPC3 is involved in signaling pathways by direct or indirect interactions with Wnts, Hedgehogs, and bone morphogenetic proteins [12,[23][24][25][26][27][28]. GPC3 appears to have a role in morphogenesis, as it has stage-and tissue-specific expression in fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…In SGB syndrome, 10% to 20% of patients described have an embryonal malignancy, including hepatoblastoma, neuroblastoma, gonadoblastoma, Wilms tumor, and hepatocellular carcinoma [4][5][6]. GPC3 exon deletions have been found in patients with SGB syndrome with embryonal malignancies, but the effect on the GPC3 protein expression and function is unknown [23,24]. As well, the GPC3 gene mutation status in sporadic hepatoblastoma has not been well studied.…”
Section: Discussionmentioning
confidence: 99%